Elaboração de produto cárneo probiótico a partir de microrganismos isolados de leites fermentados - Urnau, Diala (2008)
This study aimed to isolate and characterize probiotic strains from fermented milk and multiplies in the swine plasma medium for inoculation in Italian salamis, with the starter culture Staphylococcus xylosus isolated from artisanal salamis. Colonies count of the fermented milks was in the MRS (De Man Rogosa Sharpe Agar, Oxoid) medium by the technique of 'pour-plate'. The strains were isolated through the technical spread plate in selective medium, MRS. Individual strains were confirmed by Gram staining, catalase test and identified by kits Api 20 A and 50 CHL (Bio Merieux SA, Marcy L'Etoile, France). After, passed the tests of resistance to sodium chloride added to the MRS agar, in concentrations of 1%, 1.5%, 2%, 2.5% and 3% and resistance to nitrite and nitrate, which were conducted by the same procedure at concentrations of 80, 100, 120, 150 and 200 ppm. They also passed through of 0.3% bile and acid resistance tests, pH: 3.0, 2.5 and 2.0 of 3M HCl for 3 and 6 hours. In the second experiment, the isolate strain of Lactococcus lactis ssp lactis 2 passed through multiplication in fermented machine for use as a starter in probiotics dry fermented sausages. The probiotic strains were multiplied in plates with swine plasma medium plus agar and isolate starter Staphylococcus xylosus in BAIRD-PARKER plate. In the treatments were used as starters the S. xylosus and Lactococcus lactis, and as probiotic strains: Lactobacillus paracasei ssp paracasei 1 and Bifidobacterium spp 2. Control treatment was added with commercial starters, the Treatment 1: with isolate starters; Treatment 2: with isolate starters adding more probiotic strain a Lactobacillus paracasei ssp paracasei 1 and Treatment 3: starters more probiotic isolate strain Bifidobacterium spp 2. Were evaluated microbiological, physic-chemical and sensory aspects. Samples of fermented milks examined showed higher counts to 107CFU.g-1 and the strains were: Actinomyces israelli, 7 Actinomyces naeslundii, Lactobacillus acidophylus/jensenii, Bifidobacterium spp 2, Lactococcus lactis ssp lactis 2 e Lactobacillus paracasei ssp paracasei 1. The strains Bifidobacterium spp 2 and Lactobacillus paracasei ssp paracasei 1 were resistant to all concentrations of sodium chloride, nitrite and nitrate, and the pH of 3.0 for 3 hours and 6 hours. The L. paracasei ssp paracasei 1 showed lower counts to 106 UFC.mL-1 at pH 2.0, with 5.63 Log UFC.mL-1 in 3 hours of incubation and 3.79 Log UFC.mL-1 in 6 hours. The strain of Bifidobacterium spp 2 lost its probiotic viability after exposure of 6 hours in the pH of 2.0 and 2.5, showing reduction of 9.4 Log UFC.mL-1 to 3.67 and 4.18 Log UFC.mL-1, respectively. The strains analyzed showed resistance to bile salts and remained in a viable state after 4 hours of exposure to 0.3% of bile salts. The propagation in a culture medium made with swine plasma achieved levels of 5.52 Log CFU.mL-1 to 8.58 Log CFU.mL-1 and optical density of 0.14 to 0.882, in 27 hours of fermentation. All final physical and chemical parameters were up to standards with pHs and activities of water in accordance with the safety standards of the product. Sensory characteristics showed that the isolated strains notes were statistically equal and/or above the commercial strains and probiotics salamis had cells in a viable state for 30 days of storage.